Prototype Testing of Automatic Vessel Tracking System using Web-Based Visualization - Nazzla, Rauzatul; Hestirianoto, Totok; Pujiyati, Sri (PELAGICUS, 2022)
Automatic Tracking System is an example in the development of navigation technology that is needed in every means of transportation by land, water, or air. An example of its application in the field of fisheries management is the Vessel Monitoring System (VMS). The purpose of this study was to develop a telemetry technique particularly automatic vessel tracking system. In this study is expected to produce a prototype which can provide information about the movement of traditional fishing boats, especially in coastal areas. Prototype testing in this study was limited to the performance of a prototype based on the capability of the electronics and the resulting output data. Output data obtained by two methods: (1) the trial was stationary, and (2) mobile test. This study also examined the comparison between tracker prototype with GPS handheld. Mobile tracker marks the position automatically whenever the tool is turned on. The increasing distance between the transmitter unit to the receiver unit, the deviation would be even greater. This tool was sensitive in responding and quickly perform the recording every movement. When compared to handheld GPS, this tool has good accuracy and precision indicated by a 95% confidence interval.